PENGARUH FAKTOR SOSIO EKONOMI TERHADAP KETERLAMBATAN PENEMUAN KASUS TB DI WILAYAH KABUPATEN JEMBER - Ariyanto, Yunus (FKM - UNEJ, 2011)
Long time delay from symptoms until TB diagnosis made the patients could not be registered as suspects nor TB patients as soon, as well as consequences to patientâs prognosis and TB infection in community. Based on some interviews with TB patients from Jember, the long time delay was frequently did. The goal of this research is to analyze sosioeconomic factors of TB case finding delay of patients who residing in Jember District. This research was analytic observational study and used cluster sampling method by two months data collecting. Analysis using Spearmanâs rho correlation and calculate Prevalence Ratio (PR). Result showed that significant socioeconomic factors of TB case finding delay are annual household saving (R=-0.296) and annual household income (R=-0.249; Risk=1.4). Conclusion of this research is annual household saving, and annual household income are the factors of TB case finding delay. Â Keywords: TB, case finding, delay, socioeconomic